Global, regional, and national trends in colorectal cancer from 2010 to 2021: an analysis of the global burden of disease study 2021 - Gerun Chen; Jialin Wu; Sibo Huang; Zhenqi Gong; Huaiming Wang (Annals of Medicine, 2025)
Background Colorectal cancer (CRC) is a major global health challenge due to its high incidence and mortality rates. Understanding its epidemiological trends is essential for informing prevention and intervention strategies.Methods This study analyzed global, regional, and national CRC data from 2010 to 2021, focusing on age-standardized incidence, mortality, disability-adjusted life years (DALY), and associated risk factors. Data was sourced from the Global Burden of Disease (GBD) Study 2021 and stratified by the Sociodemographic Index (SDI).Results Globally, CRC incidence increased by 35.91% from 1,614,410 cases in 2010 to 2,194,143 cases in 2021. The mortality rate decreased from 13.37 per 100,000 in 2010 to 12.40 per 100,000 in 2021. DALY increased by 23.94%, yet the age-standardized DALY rate (ASDR) decreased by 6.88%. Notably, high SDI regions showed a downward trend in incidence and mortality, while high-middle SDI regions experienced increasing incidence but decreasing mortality. In 2021, the highest incidence was in the Netherlands (69.80 per 100,000), and the highest mortality was in Uruguay (27.46 per 100,000). Dietary and metabolic risk factors significantly contributed to CRC burden across all SDI levels.Conclusion The study reveals a complex epidemiological landscape of CRC, marked by rising incidence but declining mortality globally. These findings highlight the urgent need for targeted public health interventions, particularly in high-risk regions and younger populations, focusing on modifiable lifestyle and socioeconomic factors. Continuous monitoring and tailored prevention strategies are critical to reducing the global burden of CRC.